A nightscape preference study using eye movement analysis - Kim, Mintai; Kang, Youngeun; Abu Bakar, Shamsul (Faculty of Design & Architecture, Universiti Putra Malaysia, 2013)
The results of a nightscape preference study combining traditional survey methods and eye movement analysis are summarized. The relationship between eye movements and degree of preference for a nightscape (i.e., nighttime landscape) was analyzed. While wearing eye tracking equipment, participants (N = 23) were shown images of three landscape settings types: a spatially open setting, an enclosed setting, and a setting dominated by a path. For each landscape setting, the images were provided at four different brightness levels. Participants were also given a traditional preference survey and asked to rate each image. A significant relationship was found between participant’s eye movements and preference ratings. Results showed that people preferred brighter images of open landscapes to darker images of enclosed landscapes. These results can be explained by prospect and refuge theory. People prefer to see (prospect) dangers after dark, thus preferring brighter, more open landscape images. Participants spent more time looking at preferred images than nonpreferred images, and also spent more time looking not at light fixtures directly but at the areas surrounding them. Consistent with the affordance theory, the participants spent more time looking at objects that could be used. They also looked at images starting from the upper left and moving to the center of the images. The eye tracking study provided a detailed understanding of people’s eye movement patterns and showed great potential for use in preference studies.